Stability assessment of rock slope at Pangsapuri Intan, Cheras - Abdullah, Rini Asnida (2015)
This paper present a rock slope stability assessment at Pangsapuri lntan, Taman Bukit Permai, Cheras. This residential area was built very close to unstable rock slope, which is an abandon granite quarry. A frequent rockfall event has occurred at this slope, and the worst situation, was when a big boulder hit a taxi that parked close to the slope. A fieldwork has been carried out to gather the geological information, and unexpectedly, the rockfall has been witnesses on that day. From here, a kinematic and rockfall simulation analyses has been performed using the Rocscience software to investigate the slope condition. The kinematic analysis in Dips 5.0, the slope shows a probability of wedge failure to occur with 19%, and the RocFall has successfully simulated the rockfall event that took place on the field visit. Then, a series ofparametric study has been carried out on the rock size and shape, as to study the effect on the endpoint distance ofthe boulder. This will give a guideline to the authorities on the impact ofthe rockfall hazard and safe buffer zone. Lastly, a remedial work has been proposed with regards to the mode offailure at the study rock slope.